Destabilization of Lysophosphatidic Acid Receptor 1 Reduces Cytokine Release and Protects Against Lung Injury - Jing Zhao; Jianxin Wei; Su Dong; Rachel K. Bowser; Lina Zhang; Anastasia M. Jacko; Yutong Zhao (EBioMedicine, 2016)
Lysophosphatidic acid receptor 1 (LPA1) is a druggable target for treating pulmonary inflammatory diseases. However, the molecular regulation of LPA1 stability, a factor that critically impacts its biological activity, remains largely unknown. Here we identify two enzymes that regulate the balance of LPA1 ubiquitination and deubiquitination. Ubiquitin E3 ligase Nedd4L targets LPA1 for its site specific ubiquitination and degradation in the lysosome. Nedd4L negatively regulates LPA-LPA1-mediated cytokine release. The stability of LPA1 is up-regulated by ubiquitin-specific protease 11 (USP11), which deubiquitinates LPA1 and enhances LPA1-mediated pro-inflammatory effects. LPA1 is associated with USP11 in quiescent cells, while LPA treatment triggers LPA1 dis-association with USP11 and in turn binding to Nedd4L. Knockdown or inhibition of USP11 reduces LPA1 stability, levels of LPA1, and LPA1-CD14 interaction complex; thereby diminishing both LPA- and LPS-induced inflammatory responses and lung injury in preclinical murine models. Thus, our findings identify an ubiquitin E3 ligase and a deubiquitinating enzyme responsible for regulation of LPA1 stability and biological activities. This study provides potential targets for the development of anti-inflammatory molecules to lessen lung injury.